Realization of Actional and Formulaic Competence in Teachers’ Talk in English Language Class - Colle, Andi Tenry Lawangen Aspat; Fitriati, Sri Wuli (English Education Journal, 2019)
A number of studies have investigated the phenomenon of teachers’ talk to explain its role in the process of acquiring a target language in a classroom setting. However, studies of teachers’ talk in the field of communicative competence and it sub-competence have not much done yet. Three English teachers at SMAN 1 Semarang, SMA Nasional Karangturi Semarang, and SMA Mardisiswa Semarang were involved in this spoken discourse study to explain the realization of actional competence which proposed by Celce_Murcia et al. (1995) and formulaic competence based on the Biber et al’s. (2004) theory in teachers’ talk. Furthermore, this study also explained the relationship between those competencies. The findings of this study revealed that English teachers mostly performed actional competence in five sub-categories namely asking questions, giving instructions, explaining, reacting to interlocutors’ speech, and complementing. Related to the realization of lexical bundles, teachers’ talk mainly contained verb phrase along with dependent clauses. In contrast, lexical bundles that incorporate noun phrase and preposition fragments accounted for only a small proportion of lexical bundles. Dealing with the relationship between both competences, it revealed that there is a stock of lexical bundles on each language function. Seeing there is a relationship between both competences, the teachers must choose appropriate utterances in a given situation as the model for the students. The teachers need to maintain a balance, they are not only focused on grammar and pronunciation, but also have adequate knowledge and competence of lexical bundles for performing appropriate language functions.